Little dinosaur - Wilson, Trevor (Nelson Melbourne, 1994)
Little Dinosaur by Trevor Wilson is a charming children$1 (Bs book that follows the adventures of a small dinosaur as he navigates the prehistoric world. Despite his size, Little Dinosaur is filled with curiosity and bravery, embarking on quests to discover new friends and explore his vibrant surroundings. Through his journey, he learns important lessons about courage, friendship, and the value of being true to oneself. The story is complemented by delightful illustrations, making it an engaging read for young audiences, and it emphasizes themes of resilience and the importance of believing in one's abilities, no matter how small.s